Task and intensity alters the rms proportionality ratio in the triceps surae. Issue 6 (24th April 2015) - Ball, Nick; Scurr, Joanna Clare
ABSTRACT Introduction Dynamic movements require synergistic involvement of numerous muscles, whereby different muscular and task demands could alter the ratio of this synergistic activation. Methods Participants completed isometric, isotonic, isokinetic, and squat jump (SJ) tasks. Mean RMS EMG was collected from the medial and lateral gastrocnemius (MG, LG) and soleus (SOL), then pooled, and each muscle's activation was expressed as a percentage of the pooled activation. Results The MG contributed 9–14% more to total muscle activation in isometric and isotonic tasks versus the SJ task. The SOL contributed 8% more to the SJ task compared with the isometric and isotonic tasks. Across all tasks, MG activation was 4.0% greater than SOL and 10.5% greater than LG. SOL activation was 6.5% greater in all tasks compared with LG. Conclusions Task and intensity influences the ratio of activation in the triceps surae. Muscle Nerve51: 890–898, 2015